ANTI- OBSESSIVE COMPULSIVE ACTIVITY OF HONEY - Arzoo; Parle, Milind (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The present study aim to investigate the anti-obsessive compulsive disorder potential of honey in mice. Methods: The honey was given orally in two concentrations of 17.5 ml/kg and 35 ml/kg to mice for 21 days. The anti-obsessive compulsive activity was assessed on 21th day by in-vitro methods viz flickering-light induced obsessive- compulsive behaviour model developed in our laboratory (Patent No. 3087/DEL/2012) and marble-burying behaviour model. The biochemical estimation was also done on 21 days. Results: When honey was administered chronically for 21 days significantly reduced gnawing behaviour and marble-burying behaviour of mice. Interestingly in our biochemical estimations, both, brain serotonin and GABA level were significantly increased by honey. The anti-Obsessive compulsive activity of honey may be due to the presence of Tryptophan, which is an important precursor of serotonin in the serotonergic neurons thereby enhancing the biosynthesis of serotonin to facilitate the anti- obsessive compulsive activity. Conclusion: The present study revealed that honey possessed significant anti-OCD activity. Â 